A Critical Discourse Analysis of English Farewell Addresses by US Presidents - Ngô Thị Ngọc Anh (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
The thesis is aimed at conducting a critical discourse analysis of English Farewell Addresses by U.S. Presidents based on a combination of Fairclough’s three-dimensional model and Halliday’s Functional Grammar, thereby clarifying the language features of English Farewell Addresses by U.S. Presidents and uncovering the ideologies embedded in language.